Optimalisasi Pendidikan Anak Dan Manajerial Administrasi Pkk Desa Ngablak Kecamatan Srumbung - Fuad Yanuar Ahmad Rifai; Muhamad Sholikhun; Muhamad Khoirul Huda (Sekolah Tinggi Agama Islam Syubbanul Wathon Magelang, 2021)
Education is teaching that aims to develop the abilities that exist in students. However, many schools are currently closed due to the impact of the COVID-19 pandemic. Thus, the first work program was mentoring the student learning process in the Ngablak village. This assistance aims to make students able to carry out learning even though schools are closed. The following program is about the management of the Ngablak Village PKK. The existing Human Resources have not been able to contribute to the organization's administration. Through training in Microsoft Office Word and Excel, the goal is for PKK administration to run well. The method I use is PAR (participatory action research). This program was created because it needed to be strengthened by information obtained from the village head and not the development of existing activities. This program has had a positive impact on both the children and the administration of the Ngablak Village PKK.